Body Mass Index and multidimensional health in Chinese older adults: a moderated mediation analysis of urban–rural residence, physical activity, and depression - Pan, Hao; Hao, Ying (Frontiers in Public Health, 2025)
BackgroundIn the context of China’s accelerated aging, Body Mass Index (BMI) is a critical health metric. However, its health implications are not uniform, being profoundly shaped by structural socioeconomic divides and intricate psychosomatic pathways. This study provides an integrated analysis of BMI’s association with multidimensional health (chronic diseases, functional disability, depression) in Chinese older adults, testing the moderating role of urban–rural residence and the mediating roles of physical activity and depression.MethodsData were drawn from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS), including 11,521 older adults. We employed a suite of regression models to assess linear and non-linear associations and a Structural Equation Model (SEM) to delineate mediation pathways.ResultsA higher BMI was associated with a greater chronic disease burden, but not with ADL disability after full adjustment. Crucially, this BMI-disease association was significantly amplified in rural populations, revealing a weaker socio-environmental “buffer” against weight-related health risks. We identified a robust U-shaped relationship between BMI and depression, extending the “obesity paradox” to the psychological domain, with optimal mental well-being observed in the overweight range (BMI ≈ 28.9 kg/m2). SEM analysis revealed that depressive symptoms acted as a significant suppressor, partially counteracting the direct adverse association between BMI and chronic diseases.ConclusionThe health implications of BMI in Chinese older adults are profoundly context-dependent, challenging a one-size-fits-all approach. The findings suggest a dual insight: a psychological “obesity paradox” where moderate overweight status appears protective for mental health, and a socio-environmental moderation where the urban context appears to buffer the physical risks of higher BMI. Mental well-being emerges as a pivotal mediator in the psychosomatic pathway linking body weight to chronic illness. This evidence calls for a paradigm shift toward holistic, differentiated health strategies that integrate mental health support and are tailored to the distinct resource landscapes of urban and rural settings.